A COMPLEX SYSTEM OF TRANSPORT SERVICE AS AN EFFECTIVE WAY OF DELIVERY - Andriienko, M. M. (Science and Transport Progress, 2006)
The article is devoted to the issues of intermodal transport services, introduction of a complex system of transport service with the use of logistic systems in the operating costs management.